Commons of the South: Ecologies of Interdependence in Local Territories of Chile - Ibarra, Maria Ignacia; Guasch, Aurelia; Ojeda Villarroel, Jaime Andrés; Maulen, Wladimir Riquelme; Ibarra, Jose Tomas (My University, 2023)
In a context of global social-ecological crises, a growing number of researchers, policymakers, activists and politicians have given importance to the "commons". This is mainly because the commons are associated with a logic of regulation and collective organization over the use and conservation of those goods considered essential for both human and ecosystem co-existence. This article seeks to draw attention to the commons from the standpoint of an ecology of interdependence and understand their modes of co-existence in the Global South. We analyze four case studies along with the tensions and junctures faced by the communities and the goods that sustain their continuity over time in southern Chile, a territory where extractivism and resource exploitation have increased over the last decades. The case studies use a combination of qualitative methodologies, including document analysis, literature review, ethnographies, participant observation, interviews and other means of participatory action research with community actors. Integrative analysis and discussion of the results reveal the fluidity and dynamism of the commons of southern Chile in contexts where there is pressure for their institutionalization and/or privatization, as well as various forms of resistance on the part of the territories for their protection and revitalization.
Keywords: extractivism; global south; indigenous communities; neoliberalism; reciprocity; resistance